Zinc Oxide Nanoparticles Induce Cell Filamentation in Escherichia coli. (28th February 2013) - Gunawan, Cindy; Teoh, Wey Yang; Ricardo,; Marquis, Christopher P.; Amal, Rose
<x xml:space="preserve">Abstract</x> Zinc oxide nanoparticles (ZnO NPs) induce morphological transformation of Escherichia coli from its native rod‐shape of ≈2–4 μm to filamentous cells of 20–40 μm in length. The transient response can only be observed at up to 3.5 h proliferation, beyond which the cytotoxic effect is neutralized and the rod‐shape is restored. The filamentation is part of the bacterium SOS response to the Trojan horse‐type internalization of undissolved ZnO solids. In the absence of ZnO solids, no cell filamentation can be observed from the leached soluble zinc fraction or dissolved zinc salt.